Putting Paris into practice: Foreign aid, national ownership, and donor alignment in Mali and Ghana - Stephen Brown (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper examines the application of the first two principles of the 2005 Paris Declaration on Aid Effectiveness, namely ownership and alignment, to the cases of Mali and Ghana. It argues that Western donors and recipient governments have adopted the Paris Principles mainly in form, rather than in substance, not because of a lack of capacity but rather due primarily to a lack of will, related to interests and incentives on both sides to maintain the pre-Paris status quo. As a result, the impact on Mali's and Ghana's relationships with their traditional donors has been minimal and short-lasting. To the extent that donors and recipients have not significantly changed their practices in either Mali (a poor, fragile, aid-dependent country with low state capacity) or Ghana (a wealthier and more stable country with greater capacity), it seems unlikely that they will be able to apply the Paris Principles elsewhere. Together, the cases of Mali and Ghana, placed in a broader context, suggest that the Paris Agenda is dying.
Keywords: F35; N47; O19; O20; 330; aid effectiveness; Paris Declaration; ownership; harmonization; Mali; Ghana